Challenges experienced by Malaysian students abroad - Nurul Nabilah Yusof,; Tee, Lain-Tze; Kew, Si-Roei (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
This paper examines the challenges and adaptations faced by Malaysian students while studying abroad. To improve the quality of human capital in the country, many firms encourage Malaysian students to study overseas in various fields. The quality of education and the advancement of science and technology in foreign countries enable students to gain new knowledge that is not offered by local universities. Nevertheless, students suffer from financial stress and culture shocks when adapting to a new environment in host countries. This study examines 198 Malaysian students from numerous universities and colleges abroad, including Europe, Asia, Oceania, North America, and Middle East. The findings imply that students experience financial hardship and depend on several sources to survive when studying abroad. In addition, students face difficulties in practicing their religions and cultures, language proficiencies, and changes in food preferences. The lack of social support and the limited number of friends are also the dilemmas faced by the students in the host country.